Submerged Marine Terraces Identification and an Approach for Numerical Modeling the Sequence Formation in the Bay of Biscay (Northeastern Iberian Peninsula) - Bilbao-Lasa, Peru; Jara-Muñoz, Julius; Pedoja, Kevin; Álvarez, Irantzu; Aranburu, Arantza; Iriarte, Eneko; Galparsoro, Ibon (Frontiers in Earth Science, 2020)
Submerged sequences of marine terraces may provide crucial information of past sea level positions. However, the distribution and characteristics of drowned marine terrace sequences are poorly known at a global scale, remaining in most cases rarely studied. Using bathymetric data and novel mapping and modelling techniques, a submerged sequence of marine terraces in the Bay of Biscay was studied. The objective of this work is to identify the morphology and distribution of submerged marine terraces and the timing and conditions that allowed their preservation. To accomplish the objectives a high-resolution bathymetry (5 m) was used, which was analyzed using Geographic Information Systems and TerraceM®. The submerged terraces were identified using a Surface Classification Model, which linearly combines the slope and the roughness of the bathymetric surface to extract fossil sea-cliffs and fossil rocky shore platforms. For that purpose, contour and hillshade maps were also analyzed. Then, shoreline angles, a geomorphic marker located at the intersection between the fossil sea cliff and platform, were mapped analyzing swath profiles perpendicular to the isobaths. Most of the submerged strandlines are irregularly preserved throughout the continental shelf. In summary, 12 submerged terraces were detected with their shoreline angle between: ~ -13 m (T-1), ~ -30 and -32 m (T-2), ~ -34 and 41 m (T-3), ~ -44 and -47 m (T-4), ~ -49 and 53 m (T-5), ~ -55 and 58 m (T-6), ~ -59 and 62 m (T-7), ~ -65 and 67 m (T-8), ~ -68 and 70 m (T-9), ~ -74 and -77 m (T-10), ~ -83 and -86 m (T-11) and ~ -89 and 92 m (T-12). Nevertheless, the ones with more lateral continuity and best preservation in the central part of the shelf are T-3, T-4, T-5, T-7, T-8 and T-10. The age of the terraces has been estimated using a landscape evolution model. To simulate the formation and preservation of submerged terraces three different scenarios: (i) 20-0 ka; (ii) 128-0 ka; and (iii) 128-20 ka, were compared. The best scenario for terrace generation was between 128 Ka and 20 Ka, where T-3, T-5 and T-7 could have been formed.